Minimum support prices in India: Distilling the facts - Gupta, Prankur; Khera, Reetika; Narayanan, Sudha (Foundation for Agrarian Studies, 2021)
In recent years in India, minimum support price (MSP) and government procurement, especially of paddy and wheat, have been discussed widely, but these discussions have often drawn on evidence that is dated and incomplete. Consequently, such discussions have clouded the facts, resulting in a large number of factoids. According to these popular misconceptions, very few farmers (6 per cent only) benefit from MSP and government procurement, only large farmers benefit, and only farmers of Punjab and Haryana (and, to some extent, western Uttar Pradesh) benefit. In this article, we examine these three factoids and draw on multiple data sources to distil the facts. We argue that the existing evidence suggests a more complex picture: (1) MSP impacts 13 per cent of paddy sellers and 16 per cent of wheat sellers; (2) the geographies of procurement have expanded to new States including, notably, Madhya Pradesh, Chhattisgarh, and Odisha; and (3) although at the national level there is a bias towards large farmers, this does not imply exclusion of small and marginal farmers. In fact, a majority of the beneficiaries are marginal and small farmers on both the extensive and the intensive margins. Further, we find substantial heterogeneity by States. Haryana, for instance, has a bias in favour of small and marginal farmers. We conclude that debates on MSP and procurement must therefore take into account the changed geography of procurement and the profile of sellers, and recognise the diversity of experiences relating to procurement across States.